The relationship between the content of the potential psychopharmacological agent cyclo-L-prolylglycine in the brain of experimental animals and its antihypoxic effect - V. P. Zherdev; S. S. Boyko; K. N. Kolyasnikova (Фармакокинетика и Фармакодинамика, 2020)
In the study of strutural and intracellular distribution of cyclo-t-prolylglycine (CPG) in brain rats in experiments on mongrel white male rats, it was found that CPG determined more in the hippocampus and cerebral cortex with predominant localization in the nuclear fraction of the rat brain, in the mitochondrial and microsomal fractions CPG is distributed approximately equivalently with a small quantitative predominance in the microsomal fraction. In an experimenlt using inbred mice of 2 lines: C57Black/6 and BALB/c, differing in behavior, opposite emotional response to stress, hypoxic influence. It was shown that the content CPG mice of the C57black/6 line are 39 % larger than in the brains of mice of the stress-unstable BALB/c line, which is probably due to differences in the manifestation of its it was shown that the content of CPG in the brain of stress-resistant mice C57Black/6 more than 39 % compared with the content of GPG in brain of mice BALB/c and the relationship between the quantitative content of CPG in the brain of these experimental animals and the manifestation of its antihypoxic effect was established.